THE URGENCY OF ELECTRONIC REGISTRATION OF FIDUCIARY GUARANTEES BY NOTARY - Ni Kadek Putri Yanti; Putu Ayu Sriasih Wesna (Transpublika Publisher, 2024)
The primary goal of this study is to explore the legal underpinnings of electronically registering fiduciary guarantees through public notaries, as well as to examine the legal implications of not electronically registering fiduciary guarantees through public notaries. This study employs normative legal research methodology and utilizes both statutory interpretation and legal conceptual analysis. This research highlights that the legal foundation for electronic registration of fiduciary guarantees is established by Minister of Law and Human Rights Regulation Number 9 of 2013, which addresses the Implementation of Electronic Fiduciary Registration, and Minister of Law and Human Rights Regulation Number 10 of 2013, which outlines the Procedures for Registering Fiduciary Security Electronically. If the fiduciary guarantee remains unregistered, it will result in legal consequences, as it will lack legal force. Although a fiduciary guarantee deed executed before a notary will be considered a notarial deed, it will not hold legal validity without registration. The notarial deed will have the same legal force as a private deed because the notary has not registered the fiduciary guarantee electronically.